Can attention-deficit/hyperactivity disorder be considered a form of cerebellar dysfunction? - Isaac, Valeria; Lopez, Vladimir; Escobar, Maria Josefina (Frontiers in Neuroscience, 2025)
Attention-deficit/hyperactivity disorder (ADHD) is a heterogenous disorder, commonly described for presenting difficulties in sustained attention, response inhibition, and organizing goal-oriented behaviors. However, along with its traditionally described executive dysfunction, more than half of the children diagnosed with ADHD have been reported to show difficulties with gross and fine motor skills, albeit motor impairments in ADHD continue to be a neglected area of clinical attention. The rapidly growing field of the clinical cognitive neuroscience of the cerebellum has begun to relate cerebro-cerebellar circuits to neurodevelopmental disorders. While the cerebellum’s role in motor function, such as balance, motor coordination, and execution, is well recognized, ongoing research has evidenced its additional and fundamental role in neurocognitive development and executive function, including attention and social cognition, which are all areas of impairment commonly found in ADHD. Interestingly, neuroimaging studies have consistently shown differences in cerebellar volume and functional connectivity between ADHD and typically developing children. Furthermore, methylphenidate is known to act at the cerebellar level, as intrinsic cerebellar dopaminergic systems involved in attention and motor function have been identified. This article reviews some of the main findings linking cerebellar dysfunction to ADHD behavioral symptoms and incorporates the cerebellum as a possible neurological basis and differentiating indicator within the condition. We suggest considering more rigorous assessments in future ADHD studies, including cerebellar-associated skill evaluations to correlate with symptom severity and other detected outcomes, such as executive dysfunction, and study possible associative patterns that may serve as more objective measures for this diagnosis.